Method of speakers segmentation based on pre-segmentation - ZHENG Tie-ran; LI Hai-feng; LIU Xian; HAN Ji-qing (Tongxin xuebao)
The traditional method of speakers segmentation based on Bayesian information criterion（BIC） was improved.New speakers segmentation method adopted a pre-segmentation process to decrease calculation spending.Theory analy-sis and experiments show that the method of speakers segmentation based on pre-segmentation makes the amount of cal-culation controlled,on the premise of realizing the basic segmentation performance.